Investigation of Ground Density Distributions and Charge Form Factors for 14,16,18,20,22N using Cosh Potential - Odah, Safana S.; Ridha, Arkan R. (Iraqi Journal of Science, 2022)
The bound radial wave functions of Cosh potential which are the solutions to the radial part of Schrodinger equation are solved numerically and used to compute the size radii; i.e., the root-mean square proton, neutron, charge and matter radii, ground density distributions and elastic electron scattering charge form factors for nitrogen isotopes 14,16,18,20,22N. The parameters of such potential for the isotopes under study have been opted so as to regenerate the experimental last single nucleon binding energies on Fermi's level and available experimental size radii as well.